Motion Characteristics Analysis and Simulation of Limited Slip Differential with Curve-faced Gear Pair - Lin Chao; Ran Gui; Xu Ping (Jixie chuandong)
In order to analyze motion and anti-slip characteristics of a limited-slip differential with curve-faced gear-pair, a static model of the differential is established based on the principle of the curve-faced gear pair meshing and the differential. The influence of the order, the eccentricity and the gear pair's velocity on the differential's motion characteristics when turning is analyzed. The dynamic characteristics of the limited-slip differential with curve-faced gears are worked out with the Adams software. The results show that, compared with the ordinary cone differential, the limited-slip differential with curve-faced gears has significant anti-slip characteristics, and the anti-slip coefficient can reach 2.5. By simplifying the limited-slip differential with curve-faced gear pair, an experimental platform is built. The deflection angular velocity value of the non-circular planetary gear is obtained, which verifies its theoretical value's accuracy in the differential state.